Encyclopaedia of religion and ethics; v. 9 - Gray, Louis; Hastings, James, 1852-1922; Selbie, John A.; Gray, Louis (Edinburgh, Scotland T and T Clark, 1926)
Contents : v. 9 : Mundas - Phrygians
Keywords: Religion; Ethics